Noncoding RNAs in Neurodegenerative Diseases. (30th April 2013) - Rege, Shraddha D.; Geetha, Thangiah; Pondugula, Satyanarayana R.; Zizza, Claire A.; Wernette, Catherine M.; Ramesh Babu, Jeganathan
Abstract : Noncoding RNAs are widely known for their various essential roles in the development of central nervous system. It involves neurogenesis, neural stem cells generation, maintenance and maturation, neurotransmission, neural network plasticity, formation of synapses, and even brain aging and DNA damage responses. In this review, we will discuss the biogenesis of microRNA, various functions of noncoding RNA's specifically microRNAs (miRNAs) that act as the chief regulators of gene expression, and focus in particular on misregulation of miRNAs which leads to several neurodegenerative diseases as well as its therapeutic outcome. Recent evidences has shown that miRNAs expression levels are changed in patients with neurodegenerative diseases; hence, miRNA can be used as a potential diagnostic biomarker and serve as an effective therapeutic tool in overcoming various neurodegenerative disease processes.